A policy in stagnation: addressing inequalities in the distribution of emergency obstetric and neonatal care in Ghana - Senkyire, Ephraim; Senkyire, Gloria; Owusu, Rullmann Twi; Asiedua, Ernestina (Frontiers in Global Women's Health, 2025)
Maternal health has been a focal point of global attention since the 1980s, with initiatives like Safe Motherhood, Millennium Development and Sustainable Development Goals aiming to improve the well-being of women and infants worldwide. Despite these efforts, high maternal and neonatal mortality rates persist, particularly in middle-income countries, including Ghana, highlighting the need for urgent action. From 2000 to 2020, Ghana successfully halved its maternal mortality ratio from 499 to 263 deaths per 100,000 live births through various interventions and strategies, which is still higher than the global average. Emergency obstetric and neonatal care (EmONC) plays a vital role in preventing maternal and neonatal deaths, yet disparities in its distribution and delivery exist, particularly in Ghana. An evaluation of EmONC facilities in Ghana highlighted the challenges of infrastructure, human resources, logistics, and equipment in meeting the World Health Organisation standards for EmONC within national, regional, rural, and urban health facilities. This critical analysis paper aims to highlight these challenges and propose comprehensive solutions for improved delivery of EmONC services. Addressing these challenges requires comprehensive efforts to improve infrastructure, human resources, and supply chain logistic support. A two-pronged approach is recommended. One recommendation focuses on upgrading existing facilities and recruiting and retaining healthcare professionals in rural and underserved areas. The second recommendation calls for increasing the capability of delivery of EmONC by improving training efficiency and focusing on facilities missing only one or two of the seven key services required for basic emergency obstetric and newborn care.